Desarrollo de una propuesta de digestión anaerobia en dos fases para la obtención de biogás mediante residuos cítricos (2022)
The purpose of this degree work is to present and propose a friendly and efficient alternative for the use of organic waste, specifically for fruit peels (orange, tangerine and lemon) that nowadays represent a worldwide boom due to their final disposal and the bad use that is being given to them by being wasted and disposed of inadequately. The generation of a type of renewable energy such as biogas, which is produced from the synthesis and degradation of organic matter as a product of the alternative mechanism of bacterial metabolism, was evaluated. Initially, a search of concepts and principles on biogas production was proposed, highlighting concepts of its composition, properties, stages that comprise the process, determining factors, and at the same time, a bibliographic review of digester technologies and methane quantification methods.